Position/speed sensor-less control of wind energy conversion systems based on Rotor-Tied Doubly-Fed induction generator systems - Mbukani, Mwana Wa Kalaga (Stellenbosch : Stellenbosch University, 2019)
Thesis (PhD)--Stellenbosch University, 2019.